Case study in the era of globalised financial capital market, can Bursa Malaysia remain competitive? / Amelia Ilhami Abdul Hadi - Abdul Hadi, Amelia Ilhami (Faculty of Business and Management, 2011)
Bursa Malaysia is an exchange holding company that operates a fully-integrated exchange, offering the complete range of exchange-related services including trading, clearing, settlement and depository services towards its customers. In the era of globalised financial capital market, companies have larger choices to invest into their preferred market as there are many choices worldwide. Therefore, the case study aims to achieve its goals on analyzing the competitiveness of Bursa Malaysia. Either Bursa Malaysia is remaining its competitiveness or no longer competitive. The objectives that should be achieve after completing the case study are, to explore the competitiveness of the company, to know what are the advantages that the listed company gains while investing with the company, to explain the main contributor that makes companies still investing with the company and to analyze its fluctuate Investment Trends all over the year is affecting the rate or not. Throughout completing the case study, several interviews and observations are done as well as gathering supporting information from other resources to ensure that the information is firm and accurate. All over all, the case study would give a new breath towards how people look towards the company performance back then and nowadays.